A Contribution of Expected Utility Theory in Taxpayers’ Behavior Modeling - Ameur, Farid; Tkiouat, Mohamed (International Journal of Economics and Financial Issues, 2016)
In this paper, we analyze the attitudes of taxpayers regarding tax system. We propose an approach which combines between theory and practice. In the first step, we present a normative approach; based on a theoretical study. In order to produce an empirical knowledge of an aspect of reality we present a descriptive approach; based on a survey of different categories of taxpayers. We have released some conditions of the model of Expected Utility (EU) and we have introduced a new parameter reflecting the efficiency of tax control. Previous studies are based on a maximal efficiency tax control (100%) which is a particular case of our model. We found that for Moroccan case, the fraud is related to the size of companies; it’s more important in the big companies than small and medium enterprises. The findings will help tax authorities to achieve their goals in fighting tax fraud. Keywords: Expected Utility, Prospect Theory, Underground Economy, Tax Fraud, Tax Authority, Tax Audit, Tax Compliance, Taxpayers, JEL Classifications: C5, H3.